Optimizing inventory decisions in a multi-stage supply chain under stochastic demands - Seliaman, M. E. (Elsevier BV, 2008)
In this paper we consider the case of a three-stage non-serial supply chain system. This supply chain system involves suppliers, manufactures, and retailers. Production and inventory decisions are made at the suppliers and manufactures levels. The production rates for the suppliers and manufactures are assumed finite. In addition the demand at each end retailer is assumed to be stochastic. The problem is to coordinate production and inventory decisions across the supply chain so that the total cost of the system is minimized. For this purpose, we develop a model to deal with different inventory coordination mechanisms between the chain members. We present a numerical example for illustrative purposes.